2012
DOI: 10.1590/s1678-77572012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontal therapy on C-reactive protein level: a systematic review and meta-analysis

Abstract: The influence of oral infections, especially periodontal disease, on systemic diseases has been extensively discussed in the literature. Because periodontal disease is a persistent infection, it promotes an inflammatory response. C-reactive protein is a marker for inflammatory reactions that is frequently studied, since elevated levels of this protein are related to coronary events.ObjectiveThe aim of this study was to investigate the effect of periodontal therapy on reducing the serum levels of C-reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 20 publications
5
56
0
3
Order By: Relevance
“…A second meta-analysis of intervention trials reported similar estimates with a mean overall difference in CRP serum levels after therapy of 0.2 mg/l (95% CI, -0.15-0.55) (Ioannidou et al 2006). The most recent meta-analysis including four clinical trials reported a 0.23 mg/l reduction in CRP levels (-0.231; p < 0.0001) (Freitas et al 2012). Two additional trials performed in individuals with periodontitis and other co-morbidities including diabetes (Sun et al 2011, Chen et al 2012) confirmed the potential antiinflammatory effect of periodontal therapy also in these populations.…”
Section: Acute-phase Proteinsmentioning
confidence: 74%
See 1 more Smart Citation
“…A second meta-analysis of intervention trials reported similar estimates with a mean overall difference in CRP serum levels after therapy of 0.2 mg/l (95% CI, -0.15-0.55) (Ioannidou et al 2006). The most recent meta-analysis including four clinical trials reported a 0.23 mg/l reduction in CRP levels (-0.231; p < 0.0001) (Freitas et al 2012). Two additional trials performed in individuals with periodontitis and other co-morbidities including diabetes (Sun et al 2011, Chen et al 2012) confirmed the potential antiinflammatory effect of periodontal therapy also in these populations.…”
Section: Acute-phase Proteinsmentioning
confidence: 74%
“…After reviewing all clinical trials, authors agreed to perform metaanalysis only on markers where sufficient data were available (Table 1). One biomarker had been recently extensively reviewed and more than one systematic review with metaanalysis had been already published (Ioannidou et al 2006, Paraskevas et al 2008, Freitas et al 2012. We therefore did not include it in a meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…From the first category, many treatment studies show an effect on CRP levels in favor of periodontal treatment. Teixeira de Freitas et al 40 have concluded from a metaanalysis that nonsurgical periodontal treatment can exert a reductive effect on the serum levels of CRP. These authors propose that the time of measuring CRP and the type and the extent of periodontal treatment can influence the results of the studies dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly data collected in 2000 showed no statistical differences in the levels of C-reactive protein between groups, while the evaluation of the current oral condition reported the presence of periodontal infection being double in the control group (50%) that of the study group (24%). Levels of C-reactive protein have been widely used in research to monitor effectiveness of periodontal therapy, [3][4] and they are also used in the medical field as a risk indicator for MI. 5 The time of the MI occurrence was not reported.…”
mentioning
confidence: 99%